Ummi's Obedience in Marriage: A Critical Study of Shahnon Ahmad's Ummi & Abang Syeikhul (KEMANUSIAAN The Asian Journal of Humanities, 2012)
Malay literature can be a way by which Malay social issues are examined if indeed one subscribes to the Art for the Society movement as advocated by the Association of Malay Writers. Shahnon Ahmad's novel, Ummi & Abang Syeikhul (1992) is a relevant work with which one can contextualise the controversy that the Obedient Wives Club (Kelab Isteri Taat a.k.a Kelab Taat Suami) generated upon its establishment in Rawang, Selangor on 4th June 2011. (The setting up of a Singapore branch of Kelab Isteri Taat followed in July 2011) The club's proclamation that social ills such as prostitution and divorce could be resolved with a wife keeping her husband happy through obedient submission in the bedroom came across as suspiciously provocative. A reflective interpretation to the claim is possible with Shahnon's novel, which explores polygamous issues through the eyes of Ummi. As the third wife, Ummi's efforts in appeasing Syeikhul's insatiable sexual desires, address the conundrum of obedience in a Malay marriage. The complex emotions underlying Ummi's marital subjugation, mental conflicts and cooperative collaboration with Syeikhul's other wives illustrate that an obedient wife is in a constant battle with contradictory intrapersonal feelings despite a resignation to her own fate. This analysis offers a cultural-literary perspective of marital obedience in the interest of utilising literature as an empowering tool towards the betterment of the society.